Etnografi masyarakat Melayu di Singapura pada abad ke-19 sampai 20 Masehi - Rahmat, Syahrul; Rusli, Ris’an; Sani, Amilda (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
The construction of a port by the British in Singapore in the 19th century made this area attract the attention of sailors and traders from various parts of the world with various cultural backgrounds. Indirectly, this condition impacts the Malays, who are the original inhabitants of this island. This article discusses the cultural history of the Singaporean Malay community in the 19th to 20th centuries. It reveals the demography and culture of the people referring to 25 records of Westerners who came to visit and settled in Singapore in the 19th to 20th centuries. The discussion in this article using historical research methods, which comprise four stages, namely heuristics, source criticism, interpretation, and historiography. Data analysis uses an ethnographic approach and cultural elements by Koentjaraningrat. In the 19th to 20th centuries, Singapore’s Malay population was always second only to the Chinese. Based on a search of several records of visitors who came to Singapore, it was discovered that Singapore was divided into three parts, namely the British or European area, the Chinese area and the Malay and Keling area. The culture of society in this period comprised technological, social, economic, and artistic aspects.